Multi-isotope tracing of complex crustal fluid systems - Tyne, RL (2021)
There is significant societal concern regarding environmental issues, including ensuring safe long- term CO2 storage and safeguarding against groundwater pollution. However, the complex nature of the crustal systems mean there are still many questions surrounding fluid behaviour within the subsurface. This study utilises noble gas, stable and clumped isotopes to investigate, constrain and predict subsurface fluid behaviour within the context of CO2 storage and hydrocarbon contamination of shallow aquifers. Firstly, a novel method was developed that enabled the first noble gas analysis of multi-phase fluids. This approach was validated by comparing casing gas and produced fluids samples from oil fields in California. We then characterised the noble gas isotopes and abundances in these reservoirs and found a clear relationship between noble gas compositions and injected volumes. This allows for the prediction of both pristine and evolved reservoir compositions, which represents a crucial first step in characterising the various endmember compositions in groundwater contamination studies. Secondly, we use an integrated isotope approach to place constraints on both physical and biogeochemical processes resulting from CO2 injection into a depleted hydrocarbon reservoir CO2 storage target. We show that a significant proportion of the injected CO2 has been consumed by microbial methanogenesis and estimate a rate for this process. These findings are significant as methanogenesis can affect the trapping efficiency of a given system and thus it is a paramount consideration in site selection for future CO2 storage projects. Finally, the Paradox Basin (Colorado Plateau) is used to investigate the utility of noble gases to understand the role of basin architecture in controlling subsurface fluid composition and connectivity. Here, we use noble gas data to inform conceptual models in order to show that subsurface fluid composition and extent of fluid migration is controlled by the presence of a thick evaporite unit. The data and interpretation presented in this thesis, greatly expands our understanding of both noble gas behaviour in response to anthropogenic perturbations and the resulting processes. Additionally, this study demonstrates the utility of a multi-isotope approach for probing subsurface processes.